The question of minorities in Islam: theoretical perspectives and case studies - El-Mesawi, Mohamed El-Tahir (The Other Press, 2015)
Difference, diversity and variation among human beings, both as individuals and groups, and hence, the presence of the different Other together with the Self have always been one of the main expressions and ramifications of the original identity and essential unity of the human species. Unity in diversity, or vice versa, is one of the wonders of the creation exemplified in the creature that has been given pre-eminence and glory in the cosmos as God’s trustee and vicegerent on earth. Whatever the manifestations of difference and forms of diversity and plurality obtaining in and among human societies might be, they in no way obliterate human original identity and essential unity emanating from a God-fashioned original nature or fitrah.